Investigating the Implementation of Agile Project Management in Tech Start-ups: A Qualitative Approach - Cahyatih Kumandang; Ruslaini Ruslaini; Yessica Amelia (LPPM STIE Kasih Bangsa, 2024)
This qualitative study aims to investigate the implementation of Agile project management practices within technology start-ups. The research utilizes a qualitative approach, employing semi-structured interviews and document analysis to gather data. A purposive sampling technique is employed to select participants from a range of technology start-ups. Data analysis involves thematic analysis to identify patterns and themes in the data. The findings reveal insights into the challenges, benefits, and strategies associated with implementing Agile methodologies in start-up environments. This study contributes to a deeper understanding of Agile adoption within the dynamic context of technology start-ups, offering valuable insights for practitioners and researchers alike.